2018
DOI: 10.1016/j.bjm.2018.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Petroleum contamination and bioaugmentation in bacterial rhizosphere communities from Avicennia schaueriana

Abstract: Anthropogenic activity, such as accidental oil spills, are typical sources of urban mangrove pollution that may affect mangrove bacterial communities as well as their mobile genetic elements. To evaluate remediation strategies, we followed over the time the effects of a petroleum hydrocarbon degrading consortium inoculated on mangrove tree Avicennia schaueriana against artificial petroleum contamination in a phytoremediation greenhouse experiment. Interestingly, despite plant protection due to the inoculation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 66 publications
1
5
0
Order By: Relevance
“…Ralstonia (Di Gioia et al, 2002) and Achromobacter (Pradeep et al, 2015) have been reported as showing the ability of degrading catechol and phthalic acid, respectively, and Delftia have not previously been reported with biodegradation of salicylic acid. The contribution of the other genera with increasing percentages associated with PAHs biodegradation are supported by previous studies for Stenotrophomonas (Zang et al, 2020), Pseudacidovorax (Dealtry et al, 2018), Novosphingobium (Fida et al, 2017), Enterobacter (Lors et al, 2012), Comamonas (Qin et al, 2019), Chryseobacterium (Xiao et al, 2019), and Burkholderia (Morya et al, 2020). After the acclimation that phenanthrene and pyrene were added as carbon source, the dominant genus was Pseudomonas again in sample MBF.…”
Section: Dynamics Of the Bacterial Community During The Multisubstrate Enrichment Processsupporting
confidence: 80%
“…Ralstonia (Di Gioia et al, 2002) and Achromobacter (Pradeep et al, 2015) have been reported as showing the ability of degrading catechol and phthalic acid, respectively, and Delftia have not previously been reported with biodegradation of salicylic acid. The contribution of the other genera with increasing percentages associated with PAHs biodegradation are supported by previous studies for Stenotrophomonas (Zang et al, 2020), Pseudacidovorax (Dealtry et al, 2018), Novosphingobium (Fida et al, 2017), Enterobacter (Lors et al, 2012), Comamonas (Qin et al, 2019), Chryseobacterium (Xiao et al, 2019), and Burkholderia (Morya et al, 2020). After the acclimation that phenanthrene and pyrene were added as carbon source, the dominant genus was Pseudomonas again in sample MBF.…”
Section: Dynamics Of the Bacterial Community During The Multisubstrate Enrichment Processsupporting
confidence: 80%
“…Plasmid incP-9 plays to start the process of degradation of oil. Other research explain that the IncP-9 plasmids detected in the Genus of Ochrobactrum and Pseudomonas (Dealtry et al, 2018). From the results of this research obtained three isolates belonging to the Genus of Ochrobactrum and Pseudomonas.…”
Section: The Species Of Selected Hydrocarbonoclastic Bacteria Based Omentioning
confidence: 75%
“…The total petroleum hydrocarbons content decreased within consortia inoculating with the three species by 18.3 (mg g −1 ), 83 % of crude oil residues (1%, v/v) during 22 days of treatment (Tanzadeh et al, 2020). Dealtry et al (2018) scanned the bacterial community of petroleum hydrocarbon degrading consortium inoculated on mangrove tree Avicennia schaueriana for decontamination of artificial petroleum medium. They considered the bacterial 16S rRNA gene partial sequence and analyzed for the determination of incompatible plasmids as well as naphthalene dioxygenase genes via dot blot hybridization.…”
Section: Role Of Isolated Bacterial Species In the Crude Oil Bioremed...mentioning
confidence: 99%
“…They considered the bacterial 16S rRNA gene partial sequence and analyzed for the determination of incompatible plasmids as well as naphthalene dioxygenase genes via dot blot hybridization. They expounded the prevalence of Bacillus infantis after 10 days on incubation, with other bacterial species assigned to Pseudomonas sp., Ochrobactrum sp, and etc (Dealtry et al, 2018). Joe et al ( 2019) (Joe et al, 2019) isolated, identified a rhamnolipidproducing bacterial species (e.g., Shewanella sp.…”
Section: Role Of Isolated Bacterial Species In the Crude Oil Bioremed...mentioning
confidence: 99%